Optimization of Combustion Characteristics of Blended Coals Based on TOPSIS Method - Yingchun Liu; Hao Zhang; Xiaohui Zhang; Shan Qing; Aimin Zhang; Shuping Yang (Complexity)
The Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method is used to find optimal mixing scheme of Zhaotong lignite, Fuyuan bituminous coal, and Xiaolongtan lignite in terms of combustion performance. Comparative evaluation of different mixing schemes is also conducted, where the flammability index, comprehensive combustion characteristic index, burnout temperature, and economic costs can be used to measure the advantages and disadvantages of different mixing schemes with different parameters. Through analysis and optimization, it is found that when the lignite of Xiaolongtan, lignite of Zhaotong, and bituminous coal of Fuyuan are mixed with a ratio 2 : 1 : 2, the mixed coal has the best performance; when the lignite of Xiaolongtan, lignite of Zhaotong, and bituminous coal of Fuyuan are mixed with a ratio 0 : 2 : 1, the mixed coal has the worst performance.